2007
DOI: 10.1024/0036-7281.149.5.227
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype evaluation among young horse populations in Poland

Abstract: Five hundred young horses of the following breeds: Thoroughbred, Silesian, Malopolska, Wielkopolska, Polish Konik, Hutsul, Shetland Pony, Half-bred Anglo-Arabian, Noble Half-bred, Fjord and crosses were cytogenetically investigated. Chromosome preparations obtained after lymphocyte culture were analysed using conventional Giemsa staining and CBG-banding methods. In the case of abnormalities GTG-banding as well as FISH technique were applied. In ten mares different karyotypic abnormalities were diagnosed. One m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
2
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 14 publications
0
52
2
2
Order By: Relevance
“…A cytogenetic survey of 500 young horses was performed recently by Bugno et al (2007a). This analysis revealed that the incidence of X monosomy in mares reached 3%, but no abnormalities were found in males ( Table 8 ).…”
Section: The Romanian Programmentioning
confidence: 99%
“…A cytogenetic survey of 500 young horses was performed recently by Bugno et al (2007a). This analysis revealed that the incidence of X monosomy in mares reached 3%, but no abnormalities were found in males ( Table 8 ).…”
Section: The Romanian Programmentioning
confidence: 99%
“…The percentage of conceptions and rate of survival for monosomy X embryos in the horse is unknown [Mäkinen et al, 2001]. [Bruère et al, 1978;Miyake et al, 1979;Halnan, 1985;Bowling et al, 1987;Klunder et al, 1990;Nie et al, 1993] Thoroughbred/Anglo-Arabian cross [Chandley et al, 1975] Trakehner [Klunder et al, 1990] Warmblood [Makinen et al, 2001] Welsh Pony [Bouters et al, 1975;Chandley et al, 1975] Wielkopolska [Bugno et al, 2007] Similar to humans with Turner syndrome, affected horses exhibit normal external genitalia but gonadal dysgenesis and an underdeveloped reproductive tract. Nearly all humans with Turner syndrome have short stature due to the loss of 1 copy of the SHOX gene (short stature homeobox) [Zinn and Ross, 2001].…”
Section: Monosomy X Dsd and Its Mosaic Formsmentioning
confidence: 99%
“…[ Bannasch et al, 2007] [ Raudsepp et al, 2010] [ McGee, 2011] [ Bowling et al, 1987] Arabian Andalusian Quarter Horse Appaloosa Arabian [Miyake et al, 1979;Halnan, 1985;Bowling et al, 1987;Paget et al, 2001] [ Buoen et al, 2000;Villagomez et al, 2011] [ Raudsepp et al, 2010;Villagomez et al, 2011] [ Raudsepp et al, 2010] [ Kent et al, 1986;Bowling et al, 1987;Kent et al, 1988] Half-bred Anglo-Arabian Appaloosa Standardbred Mixed Warmblood Morgan [Bugno et al, 2007] [ Buoen et al, 2000] [ Pailhoux et al, 1995;Mäkinen et al, 1999;Makinen et al, 2001;Raudsepp et al, 2010;Villagomez et al, 2011] [ Raudsepp et al, 2010] [ Bowling et al, 1987] Half-Arabian Arabian Thoroughbred Oldenburg Pasa Fino [Gill et al, 1988] [ Buoen et al, 2000;Villagomez et al, 2011] [ Abe et al, 1999;Bugno et al, 2003;Raudsepp et al, 2010;Villagomez et al, 2011] [ Kuiper et al, 2010] [ Kent et al, 1986;Kent et al, 1988] Clydesdale Belgian Quarter Horse Quarter Horse [Klunder et al, 1990] [ Villagomez et al, 2011] [ Raudsepp et al, 2010;Villagomez et al, 2011] [ Kent et al, 1986;Bowling et al, 1987;Kent et al, 1988] Fjord Konik Polski Sta...…”
mentioning
confidence: 99%
“…In horses, the most frequent abnormalities involved sex chromosome aneuploidies, i.e. sex-reversal syndrome (XY in mares) and XX/XY chimerism (Bowling et al, 1987;Power, 1990;Bugno et al, 2007a;Lear and Bailey, 2008). In contrast, autosomal chromosome abnormalities have rarely been described (reviewed by Lear and Bailey, 2008).…”
Section: Abstract: Horse Painting Probes Fish Technique Chromosommentioning
confidence: 99%
“…When the fusion occurs after the gonads are differentiated towards the ovary, they are not masculinised as in the case of freemartin heifers from twin different-sex pregnancies (Dunn et al, 1981;Bugno et al, 1999;Jaszczak and Parada, 1999). The frequency of structural chromosome aberrations described in the horse is low, and these include autosomal translocations (Payne et al, 1968;Queinnec et al, 1975;Kent et al, 1986;Power, 1987;Herzog et al, 1988;Power, 1991;Long, 1996;Lear and Layton, 2002;, autosomal deletions (Halnan et al, 1982;McFeely et al, 1989), autosomal trisomy (Power, 1987;Klunder et al, 1989;Bowling and Millon, 1990;Buoen et al, 1997;Lear et al, Acta Veterinaria Hungarica 57, 2009 1999; Kubień and Tischner, 2002;Bugno et al, 2007a) and isochromosomes (Buoen et al, 1983;Mäkelä et al, 1994). Karyotype defects of structural type are a major breeding problem because they may significantly reduce fertility by 5% to 100%.…”
Section: Acta Veterinaria Hungarica 57 2009mentioning
confidence: 99%